Lack of APP and APLP2 in GABAergic forebrain neurons impairs synaptic plasticity and cognition - Mehr, Annika; Hick, Meike; Ludewig, Susann; Müller, Michaela; Herrmann, Ulrike; Engelhardt, Jakob von; Wolfer, David P.; Korte, Martin; Müller, Ulrike C. (Cerebral cortex, 2020)
Amyloid-ss precursor protein (APP) is central to the pathogenesis of Alzheimer's disease, yet its physiological functions remain incompletely understood. Previous studies had indicated important synaptic functions of APP and the closely related homologue APLP2 in excitatory forebrain neurons for spine density, synaptic plasticity, and behavior. Here, we show that APP is also widely expressed in several interneuron subtypes, both in hippocampus and cortex. To address the functional role of APP in inhibitory neurons, we generated mice with a conditional APP/APLP2 double knockout (cDKO) in GABAergic forebrain neurons using DlxCre mice. These DlxCre cDKO mice exhibit cognitive deficits in hippocampus-dependent spatial learning and memory tasks, as well as impairments in species-typic nesting and burrowing behaviors. Deficits at the behavioral level were associated with altered neuronal morphology and synaptic plasticity Long-Term Potentiation (LTP). Impaired basal synaptic transmission at the Schafer collateral/CA1 pathway, which was associated with altered compound excitatory/inhibitory synaptic currents and reduced action potential firing of CA1 pyramidal cells, points to a disrupted excitation/inhibition balance in DlxCre cDKOs. Together, these impairments may lead to hippocampal dysfunction. Collectively, our data reveal a crucial role of APP family proteins in inhibitory interneurons to maintain functional network activity.